Pemanfaatan Pelepah Kelapa Sawit (Elaeis guineensis) Dengan Penambahan Pati Kulit Singkong (Manihot utilissima) Dalam Pembuatan Briket - Desi Ardilla; Misril Fuadi; Azzy Hasby Prasetio (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Palm briquette briquette production as one of the fuel substitutes that began to thin and as a source of renewable alternative energy is done with the addition of cassava starch. This research used Factorial Randomized Complete Design (RAL) with two replications. Factor I is the addition of cassava husk starch with a password (P) consisting of 4 levels, namely: P1 = 5%, P2 = 10%, P3 = 15%, P4 = 20%. Factor II is the drying temperature with the code (S) consisting of 4 levels, namely: S1 = 1000C, S2 = 1100C, S3 = 1200C, S4 = 1300C. Parameters observed included heating value, moisture content, ash content. Statistical analysis result on each parameter show: The addition of Cassava Starch has a very significant different effect (P <0.01) on the calorific value. The addition of Cassava Starch gave a very significant different effect (P <0.01) on Briket Water Content. The addition of Cassava Starch gave a very significant different effect (P <0.01) on Ash Content in Briquette.Keywords : Cassava leaf, palm stem, briquettes, calorific value